2021
DOI: 10.3390/biom12010004
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-10-Producing Natural Killer Cells in the Regulatory Mechanisms of Inflammation during Systemic Infection

Abstract: Natural killer (NK) cells have the dual ability to produce pro-inflammatory (IFNγ) and anti-inflammatory (IL-10) cytokines during systemic infection, which points to their crucial role both as inflammatory effectors for infection clearance and as regulators to counterbalance inflammation to limit immune-mediated damage to the host. In particular, immunosuppressive IL-10 secretion by NK cells has been described to occur in systemic, but not local, infections as a recent immunoregulatory mechanism of inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…In addition, the Th17 cell frequency has been found to be higher in patients compared to healthy controls (20). NK cells are known to mainly secrete pro-inflammatory cytokines such as IFN-γ, but recent studies have indicated IL-17 to also be secreted by NK cells (21,22). The current study observed IL-17 expression in the total NK cell to be higher in CLL patients.…”
Section: Discussionsupporting
confidence: 41%
“…In addition, the Th17 cell frequency has been found to be higher in patients compared to healthy controls (20). NK cells are known to mainly secrete pro-inflammatory cytokines such as IFN-γ, but recent studies have indicated IL-17 to also be secreted by NK cells (21,22). The current study observed IL-17 expression in the total NK cell to be higher in CLL patients.…”
Section: Discussionsupporting
confidence: 41%
“…Moreover, it decreases pro-inflammatory cytokine production and antigen-presenting capability of macrophages and dendritic cells. Interestingly, intravenous administration of IL-10 inhibited the production of pro-inflammatory cytokine in patients with Crohn's and other inflammatory bowel diseases (IBDs) [9][10][11][12]. Therefore, beneficial effects of IL-10 therapy in psoriasis also may be expected.…”
Section: Introductionmentioning
confidence: 99%
“…High HBV DNA load, and high HBeAg and HBsAg levels may inhibit the immune cell function of patients, leading to the reduction of Flt-3L, IFN-g, IL-17A, and other cytokines with virus clearance effect (8,13,(22)(23)(24), and to the increase in the level of the most important cytokine for immunosuppression (IL-10) and other cytokines with immunosuppressive effect such as TGF-b1 (8,13,(25)(26)(27). In this study, compared with the incomplete virus response group, the complete virus response group had lower HBV DNA load, lower HBeAg and HBsAg levels, lower IL-10 level, and lower TGF-b level, which indicate that patients with complete virus response may have better immune clearance ability against virus.…”
Section: Discussionmentioning
confidence: 99%